Sophie Lee: capstone - Lee, Sophie, artist (Colorado State University. Libraries, 2026)
The artist's statement: My body of work is in the form of imaginative, graphic approach to drawing and painting on paper and canvas. I am drawn to the physical and visual process of layering marks and colors in a flexible way on to the surface. This process is both intuitive and meditative, allowing me to respond to each piece during the process. Through repetition, texture, and depth of colors, I create surfaces that speak of thoughts and emotion. Artmaking for me is a way of communicating what often feels difficult to articulate through words. It becomes a narrative where there are internal experiences and emotions. I am interested in how imagery, color, and composition can give an emotional response to the viewer. Which includes giving the discomfort and curiosity without needing verbal explanation. Every act of creation is also an act of self reflection. My work explores themes surrounding social issues, emotional states, mental health, and identity, not as fixed ideas but as ongoing questions. I navigate these subjects by blending imagination with observation, drawing from both personal experience and the broader world around me. This balance allows my work to exist somewhere between reality and abstraction. I primarily work with watercolor, gouache, ink, and oil pastel, which are mediums that offer a range of fluidity and intensity. I am interested in how these materials interact, how they bleed, flow and layer over one another. Rather than assigning a fixed narrative to each piece, I love to introduce an open ended narrative to my audiences. I invite viewers to engage with the work through their own perspectives, emotions, and experiences.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting; drawing